MAKNA TRADISI SUROAN PADA MASYARAKAT DESA AIR KULIM KECAMATAN BATHIN SOLAPAN KABUPATEN BENGKALIS - Antika, Sindy; Asriwandari, Hesti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Javanese people are generally synonymous with carrying out traditions that have been passed down by their ancestors. Likewise the Javanese people in Air Kulim Village who hold Javanese traditions namely To install suroan. Tradition suroan in this area has a unique combination of Javanese tradition with Islam. The local community does this tradition using dhikr and there are mandatory supplies called ratib water, bertih, ingkung, as well as yellow glutinous rice and core. In addition, this tradition is not only done by the Javanese community, but is also followed by the non-Javanese community. This research was carried out in Air Kulim Village, Bathin Solapan District, Bengkalis Regency, which aims to find out how the tradition is carried out suroan as well as to know the meaning of tradition suroan for the people of Air Kulim village. This study uses a descriptive qualitative research method. Data collection using in-depth interview techniques, observation, and documentation. The subjects of this research are two people key informan and five informants who participated in the implementation of the tradition suroan in the village of Air Kulim. The results of this study note that the implementation of the tradition suroan on 1 Muharram at the time after evening prayer by using syadzaliyah dhikr in an open field. Over time there is a shift in the meaning of tradition suroan which developed in people who think that the moon suro is a sacred month, there are many prohibitions and taboos that must be maintained and carrying out a series of traditional Javanese activities has turned into a religious ceremony by conducting dhikr together as a ceremony to welcome the Islamic new year. Hence, meaning suroan in the village community Air Kulim is a joint dhikr activity that is carried out in the open field every year to welcome the Islamic new year. Keywords:The SuroanTradition, Symbolic Interactionism, The Meaning of Suroan